Alcohol use during pregnancy in rural Lesotho: "There is nothing else except alcohol". (December 2021) - Marlow, Marguerite; Christie, Hope; Skeen, Sarah; Rabie, Stephan; Louw, Jacobus G.; Swartz, Leslie; Mofokeng, Shoeshoe; Makhetha, Moroesi; Tomlinson, Mark
Abstract: Objective: Reducing alcohol use during pregnancy is a pressing public health priority in Sub-Saharan Africa, but insight into the factors that influence prenatal drinking practices is lacking. This study investigated perceptions of, and motivations for, alcohol consumption during pregnancy and associated practices in a rural district of Lesotho. Methods: A combination of purposive and snowball sampling methods were used to identify pregnant women and mothers with young children from the general community, as well as from alcohol-serving venues. Between September 2016 and March 2017, a trained data collector conducted in-depth interviews with 40 women on reasons why pregnant women drink, what they know about the risk of drinking alcohol during pregnancy, and perceptions of women who drink during pregnancy. Results: Sixty-five percent of women ( n = 26) reported that they consumed alcohol during pregnancy. Findings were clustered into four themes: 1) alcohol use in daily and cultural life; 2) alcohol as relief from stress and hunger; 3) alcohol's effect on the baby; and 4) access to information about alcohol consumption. Our data suggest that alcohol use was a prominent feature of daily life and a key part of traditional events and ceremonies. Other than potentially harming the baby through falling on their stomachs while inebriated, women did not mention other risks associated with prenatal alcohol use. Rather, there were prominent beliefs that drinking alcohol – home-brewed alcohol in particular – had cleansing or protective benefits for the baby. Experiences of food insecurity were prominent, and women reported that alcohol helped curb their hunger and allowed them to save food to give to their children. Conclusions: Within this context of chronic poverty and food insecurity, alcohol use during pregnancy will continue to represent a valid, though tragic choice if the structural conditions and current social arrangements that facilitate prenatal alcohol use remain unchanged. Highlights: Women consumed alcohol during pregnancy as a source of relief from stress and poverty. Experiences of food insecurity were prominent, and alcohol helped curb women's hunger. Drinking alcohol was a key part of social and traditional events, facilitating prenatal alcohol use. Consuming alcohol during pregnancy was perceived as beneficial and perceptions of risk was minimal.